China Trade Expansion: A Case Study of Vietnam - Huynh, Vy Dang Bich; Nguyen, Phuc Van; Nguyen, Quyen Le Hoang Thuy To; Nguyen, Phong Thanh (International Journal of Economics and Financial Issues, 2017)
Vietnam encountered the unexpected trade deficit with China in the recent years. Upon establishment of the ASEAN Economic Community on December 31st, 2015, the import tax rates of the regional countries have been reduced significantly. This facilitates the quality goods from the ASEAN countries overflowing into Vietnam. Nevertheless, a few research and analysis on the challenge of importing goods from China under the regional economic integration. To settle these issues, this paper analyzes the China‘s market expansion into Vietnam. In addition, it also compares the Vietnam’s import structure from China and other countries in ASEAN. The results showed that China is always the top export partner of Vietnam, particularly, machinery and raw materials. Keywords: Economics, import structure, China, Vietnam JEL Classifications: A1, D5, F1